Ketidakpatuhan Dokter Spesialis Obsgin dalam Melaksanakan Clinical Pathway - Munjari, Munjari (Syntax Idea, 2021)
The purpose of this study is to data who obsgin specialists do not comply in clinical pathways in every way sectio caesaria medical education services. Qualitative research type by way of interview indepth how it works. The results of the study idawan each informant already understand the purpose and purpose of clinical pathways but has not been informed with four reasons, namely not in, the request of doctors, management of the word, and the unclear existence of the order. What this does leads to changes in quality and cost and patient safety so that hospital performance is patient.